Effectiveness of a participatory ergonomics intervention to improve musculoskeletal health: A solomon four-group study among manufacturing workers in selangor, Malaysia - Baharudin, Mohd Rafee; Abdul Rahman, Anita (Springer International Publishing AG., 2017)
MOHD RAFEE BIN BAHARUDIN (A03654) / / ANITA BINTI ABDUL RAHMAN /